Pelaksanaan Bimbingan Belajar Bahasa Indonesia Menggunakan Metode Discovery Learning Pada Materi Laporan Hasil Observasi - Isnawati Isnawati (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This study aims to determine the implementation of Indonesian tutoring through LHO using the Discovery Method. This research uses quantitative research methods. This research is descriptive in nature, namely a research method that seeks to describe and interpret objects in accordance with what they are without intending to make general conclusions. The location of the research was carried out at MA Assholihiyah class X. The research subjects were determined using a purposive sampling technique, namely the technique of taking samples of data sources with certain considerations. the number of samples in this study were all students of class X, totaling 20 students. The research subjects totaled 20 male students 6, female students 14. The instrument used in collecting research data was to use tests distributed online which were then followed up by direct observation to obtain accurate and maximum results. The results showed that after applying tutoring using the Discovery Learning method, student learning outcomes increased with an average student learning outcome of 82.36 in cycle III and student mastery of classical learning reaching 84.84.